The magnetocaloric effect of iron-based soft magnetic alloys - Law, Jia Yan. (2012)
The magnetocaloric effect (MCE) describes the temperature change induced in a magnetic material when it is adiabatically magnetized and demagnetized. This effect can be large at temperatures and magnetic fields corresponding to magnetic phase transitions. This phenomenon can be employed in novel energy efficient refrigeration systems which can decrease global energy consumption and eliminate the use of ozone depleting gases. The systems studied so far employ gadolinium alloys which are expensive, available in limited quantities and corrode easily. Development of new, affordable and corrosion resistant magnetocaloric materials (MCM) are needed for most commercial applications. Hence, the MCE of Fe80-xB12Cr8REx (RE=La, Ce or Gd, x = 1-15 at.%) alloys was investigated. Fe80B12Cr8 alloys are the base alloys studied in this work since they exhibit reasonably good MCE near room temperature (RT), with boron and chromium aiding in glass formation and corrosion resistance, respectively. Gd, which is well known for its good MCE near RT, was added as an alloying element to Fe-B-Cr base alloys. La and Ce were also selected to study the influence of light rare earth (RE) additives on the MCE of Fe B Cr RE alloys. These RE additions were used to tune the Curie temperature (T_C). T_C decreased, increased and remained relatively constant with increasing Ce, Gd and La content, respectively. The T_C was adjusted near RT with relatively constant peak magnetic entropy change (|peak ΔS_M|) for ~5at.% addition of Ce to Fe-B-Cr amorphous alloys. Enhanced refrigerant capacity (|RC|) was also observed. Both the phenomenologically constructed universal curve for ΔS_M(T) and magnetic field dependence of |peak ΔS_M| and |RC| showed that these alloys exhibited similar critical exponents. The good RC values, soft magnetic behavior and tunable T_C make Fe-B-Cr-RE amorphous alloys attractive for multilayer active magnetic regenerators. The influence of crystallization on the MCE of Fe-B-Cr-Gd alloys was studied by partially crystallizing Fe79B12Cr8Gd1 and Fe75B12Cr8Gd5 alloys. The |peak ΔS_M| of these partially crystalline alloys compare favorably to Mo-containing Finemet-type alloys, Fe-Nb-B and Fe-Cr-Nb-B alloys.